NILAI RELIGIUS DAN TOLERANSI DALAM FILM ANIMASI “NUSA DAN RARA” - Alina Ningrum Sayekti; Nur Fajrie; Much. Arsyad Fardani (Universitas Muria Kudus, 2022)
This study aims to analyze the storyline and the meaning of religious values and tolerance, and to find out the response of children after watching the animated film